Role of melatonin receptor 1A and pituitary homeobox‐1 coexpression in protecting tubular epithelial cells in membranous nephropathy. Issue 1 (25th March 2018) - Huang, Yen‐Sung; Lu, Kuo‐Cheng; Chao, Tai‐Kuang; Chen, Jin‐Shuen; Chen, Ann; Guo, Cheng‐Yi; Hsieh, Hsin‐Yi; Shih, Hsiu‐Ming; Sytwu, Huey‐Kang; Wu, Chia‐Chao
Abstract: Membranous nephropathy (MN), a type of glomerular nephritis, is one of the most common causes of nephrotic syndrome in adults. Although it is known that melatonin plays a protective role in MN, the role of melatonin receptors in the pathophysiology of MN is unclear. Using an experimental MN model and clinical MN specimens, we studied melatonin receptor expression and found that melatonin receptor 1A (MTNR1A) expression was significantly downregulated in renal tubular epithelial cells. Molecular studies showed that the transcription factor pituitary homeobox‐1 (PITX1) promoted MTNR1A expression via direct binding to its promoter. Treatment of a human tubular cell line with albumin to induce injury resulted in the stable reduction in MTNR1A and PITX1 expression. PITX1 levels were significantly downregulated in tubular epithelial cells from mice MN kidneys and MN renal specimens. Knockdown of MTNR1A, PITX1, or cyclic adenosine monophosphate‐responsive element‐binding protein (CREB) decreased E‐cadherin (CDH1) expression, but upregulated Per2 and α‐smooth muscle actin (αSMA) expression. Blockade of the MTNR1A receptor with luzindole in MN mice further impaired renal function; this was accompanied by CDH1 downregulation and Per2 and αSMA upregulation. Together, our results suggest that in injured tissue, decreased PITX1 expression at the MTNR1A promoter regions leads to decreased levels of MTNR1A in renal tubular epithelial cells, which increases the future risk of MN.